Fungal Endophytes: Beyond Herbivore Management - Bamisile, Bamisope S.; Dash, Chandra K.; Akutse, Komivi S.; Keppanan, Ravindran; Wang, Liande (Frontiers in Microbiology, 2018)
The incorporation of entomopathogenic fungi as biocontrol agents into Integrated Pest Management (IPM) programs without doubt, has been highly effective. The ability of these fungi pathogens such as Beauveria bassiana and Metarhizium anisopliae to exist as endophytes in plants and protect their colonized host plants against the primary herbivore pests has widely been reported. Aside this sole role of pest management that has been traditionally ascribed to fungal endophytes, recent findings provided evidence of other possible functions as plant yield promoter, soil nutrient distributor, abiotic stress and drought tolerance enhancer in plants. However, reports on these additional important effects of fungal endophytes on the colonized plants remain scanty. In this review, we discussed the various beneficial effects of endophytic fungi on the host plants and their primary herbivore pests; as well as some negative effects that are relatively unknown. We also highlighted the prospects of our findings in further increasing the acceptance of fungal endophytes as an integral part of pest management programs for optimized crop production.